The main problems of interrelations' mutual conditionality of the national human capital, defense industry complex and aerospace defense - D. O. Salyukov (MGIMO University Press, 2013)
The article gives the review and highlights the importance of the system consisting of such broad and key concepts for the government, as the national human capital, defense industry complex and aerospace defense. The article also gives the analysis of the correlation of elements of this system and their unconditional necessity in the modern state as obligatory attributes of safety of the country in the modern world. The problems of the system and the influence of "soft forces" are exemplified by the current situation in the Russia Federation.